THE TECHNIQUES AND ACCURACY IN THE TRANSLATION OF CULTURAL WORDS IN GEORGE ORWELL’S ANIMAL FARM - Vina Saphagus Tieas; Eko Budi Setiawan; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2017)
This study aimed to analyze the techniques employed to translate the cultural words and their accuracies. The data was obtained from a classic novel written by George Orwell entitled Animal Farm and its Indonesian version under the same title translated by Bakdi Soemanto. This research applied descriptive-qualitative method. As the population of this research was too large, this research applied purposive sampling. The techniques employed in translating the cultural words were judged by using translational equivalent method. While, the degree of accuracy was determined by the employment of distribusional method. The finding of this research presented ten techniques employed to translate the cultural words, namely adaptation (15), amplification (7), borrowing (14), calque (7), description (11), generalization (11), modulation (2), particularization (3), reduction (4), and transposition (6). In terms of accuracy, the renderings were classified into three degrees. They were accurate (47), less accurate (30), and inaccurate (3). Most of the cultural words were translated accurately and only a small number of the words was translated inaccurately. Keywords: Cultural Words, Translation Techniques, Accuracy in Translation